Front Cover: Triplet Harvesting with a Simple Aromatic Carbonyl (ChemPhysChem 17/2017). Issue 17 (5th September 2017) - Torres Ziegenbein, Christian; Fröbel, Sascha; Glöß, Maria; Nobuyasu, Roberto S.; Data, Przemyslaw; Monkman, Andrew; Gilch, Peter
Abstract : The Front Cover picture shows a chimera illuminated by the fluorescence emission of thioxanthone, the aromatic carbonyl studied here. Due to singlet and triplet excitations in close energetic vicinity, its photophysics exhibits a chimeric behavior. More information can be found in the Communication by P. Gilch and co‐workers onpage 2314 in Issue 17, 2017 (DOI:10.1002/cphc.201700683 ).